Analisis Kebersihan Lingkungan di Pondok Pesantren Putri Tahfidzul Qur’an Sirojul Ulum Semanding Pare - Mustajib (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2020)
A clean environment is certainly a dream for everyone, both in the home and in the environment they work, to realize the necessary hygiene of self-awareness in every line of life to make cleanliness not only a dream but need embodiment action. For cleanliness in the boarding school environment, because the environment is a place for students who require the knowledge that needs beauty, comfort, cleanliness and certainly not less important is a healthy environment, in this article, we will focus on the cleanliness in the environment of the Pondok pesantren Princess Tahfidzil Qur'an sirojul ulum semanding pare. How the students ' custom characteristic in handling environmental hygiene, care, and treatment on a daily basis.